On The E. Study Maps For The Dual Quaternions - Yuce, Salim (TSING HUA UNIV, DEPT MATHEMATICS, 2021)
In this study, the generalization of the well-known E. Study map for unit dual quaternion vectors in H-D(3) is obtained, where D and H-D are sets of dual numbers and dual quaternions, respectively.
Keywords: Mathematics